PENGEMBANGAN SISTEM INFORMASI MANAGEMEN MASJID UNTUK PENGURUS MASJID SE-BANJARMASIN UTARA - MUHAMMAD, ALI; HIDAYAH, YULIANTI; CITRAWATI LESTARI, NANA (Inovate, 2020)
The mosque is a center for education, teaching, and development of science, a community information center, acenter for the collection and distribution of zakat, infaq, and shodaqoh. Observation results indicate that 80% ofmosques in the North Banjarmasin city have a conventional management and information delivery (not displayedtransparently using information systems). The objective of the study is to facilitating the mosque administrator inmanaging and delivery information about the mosque using the mosque management information system. Theresults of this study showed that the proposed mosque management information system had a 100% informationsystems success in terms of security, content, accuracy and format of the management information system. Thelowest percentage of information systems success is 82% in terms of system quality at ease of use.Keyword: Management, MIS, Mosque.